DOCUMENTAL RESEARCH ABOUT COMPUTATIONAL THINKING IN HIGHER EDUCATION: ANALYSIS OF PEDAGOGICAL PROJECTS OF COMPUTER SCIENCE TEACHER EDUCATION PROGRAMS IN BRAZIL: A DOCUMENTAL RESEARCH ABOUT COMPUTATIONAL THINKING IN HIGHER EDUCATION: ANALYSIS OF PEDAGOGICAL PROJECTS OF COMPUTER SCIENCE TEACHER EDUCATION PROGRAMS IN BRAZIL (Revista Contexto & Educação, 2021)
The growing integration of computational thinking (CT) in school education demands policies for teacher education. While several projects in academic, institutional and governmental contexts are taking place, little has been done so far in preservice teacher education, i.e. integrating CT to pedagogical projects of teacher education programs. The first initiatives in this sense are noticed in computer science (CS) teacher education programs, which have a key role in promoting CT in schools. This article presents documental research from the e-MEC platform, and based on pedagogical projects of  Brazilian CS teacher education programs, available online, which investigates how CT is being integrated into the projects. Results indicate that CT has been presented as an essential ability for all, and mainly as a tool for problem solving in any knowledge area, with the CS teacher having the responsibility of promoting it in schools. Despite the low number of CS teacher education programs which integrate CT in their pedagogical projects so far, we believe that they indicate on-going transformation, which demands time, given the complexity of reformulating pedagogical projects.
Keywords: Computational thinking; Higher education; Computer Science teacher education; Teacher education programs